Better together : 8 ways working with women leads to extraordinary products and profits - Sposato, Jonathan, 1967- (Wiley, 2017)
"It is the year 2017 and gender equality and womenthrivingin work place without fear of sexual harassment or discrimination is the #1 unsolved social issue of our time. Better Together: 8 Ways Working with Women Leads to Extraordinary Products and Profitsoffers a rare and startling look at the business world through the lens of an expert looking in and plots out how ALL types of businesses can gain a competitive advantage and excel past competitors by simply nurturing an equal blend of men and women on leadership teams and staff. It focuses on powerful and implementable solutions that any CEO, manager, or team leader can put to use to ensure that women thrive within the organization, leading to the business being more successful, customers happier, and employees more fulfilled. Author Jonathan Sposato knows the challenges facing women in startup tech and venture capital today because he specifically builds his companies with-out those obstacles. He credits the unprecedented success of his businesses on his brand of gender-balanced culture, and in this fully practical guidebook to his celebrated style of team building, he puts his eight secrets to profiting through diversity in your hands. These secrets are not just for tech companies, but for teams and companies in ANY industry. It is the culmination of extensive research on the many issues that affect gender equality (or lack thereof) in the workplace, exhaustive interviews with many powerful female CEOs and executives who have been brave in sharing stories of their own personal struggles andtriumphs, as well as Jonathan's own experiences as a male entrepreneur, CEO, and angel investor in supporting the advancement of women in business. The book also shows us why thats not only the right thing to do, but the smart thing to do economically. With the same entertaining and informative delivery that makes him a sought-after speaker worldwide, Jonathan walks you through adjusting your own culture to open the FULL potential of your workforce. The data will amaze you and the real-world voices will inspire you, and withBetter Togetheryou can achieve more success with more women on your team. If you care about inclusivity and beating the forces that prevent it, you will want to read this book. About the Author;Jonathan Sposato is chairman and co-founder of Geekwire, PicMonkey, and WeCount.org, and in general, a serial startup founder. Since his early days as a high-performingplayer on the first Xbox and Xbox games business, hes gone on to add numerous awards for innovation, voted CEO of theYear for Picnik.com, receiving the University of Washingtons Man of Integrity award, and becoming the only person to sell two companies to Google. He recently promised all his future investments to female-founded companiesanother first in the technology industry."--